Evaluation of the effect of strontium and tungsten carbide on the microstructure evolution, tribological and mechanical behaviour of Al-Zn-Mg-Cu-5Sr-WC metal matrix composite - JOHNSON, Jeffin; RAJA, Rosari (Journal of Metals, Materials and Minerals, 2024)
The present study focused on the experimental investigation of the metallurgical, tribological, and mechanical behavior of the developed Al-Zn-Mg-Cu-Sr-WC (Al7075-Sr-WC) metal matrix composite. The effect of the reinforcements such as strontium and tungsten carbide (WC) along with a 2 wt% magnesium as the wetting agent during the stir casting of the synthesized aluminum metal matrix composite (MMC) was investigated by varying the weight percentages. The microstructure examination was characterized using field emission scanning electron microscopy (FE-SEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy dispersive spectroscopy (EDS) techniques. Wear analysis and mechanical testing were conducted to study the effect of WC particles in the matrix phase by examining their wear rate, tensile strength, proof strength, and hardness values. From the mechanical and tribological tests, it was observed that there was an increase of 55% in hardness and 43% in tensile strength, along with a 31% reduction in wear rate. The secondary phases revealed from XRD analysis lead to more hardness along the refined grain boundaries. The tensile strength of the composite initially increased with a 3 wt% of WC and 5 wt% strontium due to hindrance to the dislocation movement but decreased with more reinforcement particles caused by brittleness. The hard WC particles presence has reduced the wear rate significantly due to its resistance towards abrasive wear and lubricating effect. The unique combination of a grain refiner and a binder helped develop a novel composite with superior characteristics that could replace many aerospace components made up of Al7075 alloy.